THE EFFECT OF AN EXTRACURRICULAR RECREATIONAL ACTIVITIES CURRICULUM ON REDUCING SCHOOL STRESS AMONG MIDDLE SCHOOL STUDENTS AGED (13-15 YEARS) - Marwah Ali Hamzah (Fakultas Kedokteran Universitas Sultan Ageng Tirtayasa, 2026)
The purpose of this paper is to develop a curriculum for extracurricular recreational activities for middle school students and to identify the curriculum's impact on reducing school-related stress among middle school students aged 13-15 years. The researcher used the experimental method with a two-group equivalent experimental design, as it suited the nature of the research problem. The research community consisted of middle school students aged 13-15 years at Al-Najat Girl Secondary School during the 2024-2025 academic year, totaling (237) students distributed across three grade levels as follows: first intermediate (77) students, second intermediate (91) students, and third intermediate (69) students. A random sample of (33) students from the second intermediate grade, section (B), was selected and divided into two groups (experimental and control), with (15) students in each group. Three students were excluded due to their lack of attendance. The researcher used a scale designed consisting of (55) items distributed across six domains. To achieve the research objectives, the researcher adopted the following procedures in preparing the curriculum for extracurricular recreational activities. The study selected extracurricular activities as a means of implementing the curriculum. Three days each week were designated, with each learning unit lasting 45 minutes. A curriculum consisting of 24 remedial learning units was developed over a two-month period. The researcher incorporated competitive exercises and employed a free performance method for students to execute the exercises and skills under the supervision of the research team and the researcher. The students completed the skills-based assignments. The most important conclusion reached was that the recreational activities curriculum developed by the researcher played a significant role in reducing school-related stress among the research sample.